2019
DOI: 10.1016/j.apenergy.2019.04.089
|View full text |Cite
|
Sign up to set email alerts
|

Energy-saving opportunities of direct-DC loads in buildings

Abstract: Despite the recent interest in direct current (DC) power distribution in buildings, the market for DC-ready loads remains small. The existing DC loads in various products or research test beds are not always designed to efficiently leverage the benefits of DC. This work addresses a pressing need for a study into the development of efficient DC loads. In particular, it focuses on documenting and demonstrating how to best leverage a DC input to eliminate or improve conversion stages in a load's power converter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 41 publications
0
30
0
1
Order By: Relevance
“…As remedies for pump-based systems, conventional non-pump-based sources of heating and cooling of homes and hot water have been proposed by various researchers. Gerber et al [47] investigated the use of direct current (DC) as an efficient source of energy There are several sources of energy that serve various purposes in residential buildings. Bee et al [37] assessed the potential of self-consumption for photovoltaic systems and air-source heat pumps as sources of energy for residential heating and cooling in European climates.…”
Section: Overview Of Energy Demand In Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As remedies for pump-based systems, conventional non-pump-based sources of heating and cooling of homes and hot water have been proposed by various researchers. Gerber et al [47] investigated the use of direct current (DC) as an efficient source of energy There are several sources of energy that serve various purposes in residential buildings. Bee et al [37] assessed the potential of self-consumption for photovoltaic systems and air-source heat pumps as sources of energy for residential heating and cooling in European climates.…”
Section: Overview Of Energy Demand In Buildingsmentioning
confidence: 99%
“…As remedies for pump-based systems, conventional non-pump-based sources of heating and cooling of homes and hot water have been proposed by various researchers. Gerber et al [47] investigated the use of direct current (DC) as an efficient source of energy for selected appliances (including cooling gadgets such as bath fans, refrigerators) in buildings. They showed that, though direct-DC loads are generally efficient, the efficiency is higher in loads that are unequivocally designed for DC from the ground up relative to an alternating current (AC) modification.…”
Section: Overview Of Energy Demand In Buildingsmentioning
confidence: 99%
“…LEDs, which are preferred because of their features such as making efficient lighting with less energy consumption, become more widespread for the illumination applications [3][4][5][6][7][8]. LED illumination is not only used in the night but also applied and used in offices, schools, industrial installations which are active during daylight [9].…”
Section: Introductionmentioning
confidence: 99%
“…In new recent research performed by Lawrence Berkeley National Lab economic studies proof that the changing from an AC bus to a DC bus is advantageous. Energy efficiency studies in industrial systems and commercial buildings have demonstrated that the use of DC bus leads to improved performance as claimed in [22]- [31], although no results are shown when it comes to industrial plants.…”
Section: Introductionmentioning
confidence: 99%